Unpacking Routine Program Monitoring-Sustainability of Agricultural Projects Funded by Non-governmental Organizations Nexus. An empirical Study in Bungoma County, Kenya - MULI, E. K.; Kyalo, K. D.; Ondeko, N. R. (Advances in Social Sciences Research Journal, 2020)
Guided by systems theory, this study investigated how routine program monitoring influences the sustainability of agricultural projects. The analysis included the following tests: means, frequencies and standard deviations for descriptive analysis while inferential statistics was conducted by the use of correlations, and linear regression. The study had the following findings: Sustainability of agricultural projects had a general mean (GM) of 24.7080 and a general (SD) of 4.30998 showing that agricultural projects were not sustained. Small standard deviation showed a consensus among participants on this issue. For routine program monitoring, the general mean score for all items was 31.2336 with a general standard deviation of 4.82984. The implication of this mean score and standard deviation in respect to the study is that there was general agreement in opinion among participants that organizations utilized monitoring and evaluation system in terms of routine program monitoring. The results from interview guides supported the quantitative results, by agreeing that organization indeed utilized monitoring as required. Project managers were convinced that organizational monitoring system was in good condition, the only challenge that was expressed by project managers concerning monitoring system is poor utilization of collected data to take corrective measures. It was said that data collected from monitoring was rarely used to make project improvements. Routine program monitoring was found to have a very small positive correlation with the sustainability of agricultural projects which was not statistically significance. H0: was not rejected with r= 0.059, . This shows that the regression model was not fit.